2014
DOI: 10.1186/1471-2164-15-462
|View full text |Cite
|
Sign up to set email alerts
|

Effects of functional feeds on the lipid composition, transcriptomic responses and pathology in heart of Atlantic salmon (Salmo salar L.) before and after experimental challenge with Piscine Myocarditis Virus (PMCV)

Abstract: BackgroundCardiomyopathy syndrome (CMS) is a severe cardiac disease of Atlantic salmon (Salmo salar) recently associated with a double-stranded RNA virus, Piscine Myocarditis Virus (PMCV). The disease has been diagnosed in 75-85 farms in Norway each year over the last decade resulting in annual economic losses estimated at up to €9 million. Recently, we demonstrated that functional feeds led to a milder inflammatory response and reduced severity of heart lesions in salmon experimentally infected with Atlantic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…Functional feeds are feeds that beyond their nutritional composition are formulated with health‐promoting features (Martinez‐Rubio et al., ). The health‐promoting function is typically gained either by altering the quantity or ratios of existing ingredients or by adding new ingredients.…”
Section: Prevention and Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional feeds are feeds that beyond their nutritional composition are formulated with health‐promoting features (Martinez‐Rubio et al., ). The health‐promoting function is typically gained either by altering the quantity or ratios of existing ingredients or by adding new ingredients.…”
Section: Prevention and Controlmentioning
confidence: 99%
“…A study published in 2014 concluded that salmon fed trial diets with lower lipid content (~18% versus ~31%), and higher Ω‐3/Ω‐6 ratio (PUFAs) (~4 to ~1.4) than in a reference diet, performed better after intramuscular challenge with PMCV. In one trial diet, histidine was added as this amino acid plays important roles as buffer and antioxidant in muscle cells (Martinez‐Rubio et al., ). The study concluded that lipid content and composition may have an immunomodulatory effect, resulting in a milder and delayed immune response after PMCV infection, and significant reduction in tissue damage during CMS outbreaks.…”
Section: Prevention and Controlmentioning
confidence: 99%
“…Furthermore, aberrations in lipid metabolism upon ingestion of plant oils may compromise fish health (Kjær et al., ; Todorčević et al., ). Recent research has also shown that salmon fed n ‐6 fatty acids are more susceptible to viral diseases (Martinez‐Rubio et al., , ). There is an urgent need to find novel feed ingredients, which are ideally not used directly as human food, for the aquafeed industry.…”
Section: Introductionmentioning
confidence: 99%
“…The lower mortality and large reduction in runts among fish fed the test diet compared to those fed the control diet, is an important observation in this study. Previously, diets with reduced lipid content have been shown to reduce the inflammatory responses and associated heart lesions in salmon experimentally challenged with Atlantic salmon reovirus (ASRV) and piscine myocarditis virus (PMCV), that are associated with HSMI and CMS, respectively (Martinez‐Rubio et al., , ). In these studies, however, the reduced dietary lipid content was combined with increased levels of polyunsaturated fatty acids (PUFA), eicosapentaenoic acid (EPA) and phospholipids, and the dietary causative effects could not be separated.…”
Section: Discussionmentioning
confidence: 99%
“…The effectivity of some of these functional feeds has been reported in scientific studies. In line with this, low‐lipid diets containing high levels of specific fatty acids have been used as a potent tool to control HSMI and CMS in Atlantic salmon by modulating tissue fatty acid composition and eicosanoid production (Martinez‐Rubio et al., , ). Commercial available “PD feeds” are frequently used within the SAV3 endemic zone (Jansen et al., ), and these feeds are often formulated to have lower lipid and higher protein content than standard diets.…”
Section: Introductionmentioning
confidence: 99%